The determination of cell surface phenotypes of lps-stimulated u937-derived microparticles - Jamaludin, Nur Hidayah (Universiti Sains Malaysia, 2016)
Microparticles (MP) are cell vesicles that are produced by cells such as endothelial cells and platelets. These MP productions are triggered under certain circumstances such as apoptosis and activation of cells. The purpose of this project was to characterize the cell surface phenotype of monocytic MP (mMP) derived from 1)937 cells after being stimulated with LPS. In this study, U937 cells were stimulated with 1 ug/ml LPS for 18 and 24 hours. After LPS stimulation, cell viability was detected using Trypan blue exclusion on LPSstimulated U937 cells. Both cell pellet and mMP were stained with CD14, CD11b and HLADR before being analysed by flow cytometry. As for mMP detection, cells were co-labeled with Annexin-V. Flow cytometry analysis showed that both U937 cells and mMP express CD11b and HLA-DR with slight expression of CD14. As mMP were originated from U937 cells, it is possible for both cells and mMP to express the same surface phenotypes. Furthermore, mMP were also positive for Annexin-V which is a marker of phosphatidylserine (PS). This PS is a structure that belongs to the cell surface which is exposed after cell membrane asymmetry being destroyed in apoptosis by LPS. As mMP structure was derived from the cell membrane of U937 cells, it is possible for mMP to have PS expression on their surfaces which resembled their mother cells. In summary, LPS stimulated U937 cells to produce mMP under the condition of cell death or apoptosis as LPS mimicking inflammation. In future, these mMP can act as specific biomarkers for inflammation and this project could be the preliminary studies that characterized the mMP.